The resilience trajectories of women accountants on the boards of publicly traded companies in Brazil - de Campos Cursino, Adelia Marina; Durso, Samuel de Oliveira (Revista de Educação e Pesquisa em Contabilidade (REPeC), 2025)
Objective: To analyze the career paths of women accountants serving on the boards of companies listed on the Brazilian stock exchange in light of resilience theory. Method: Thirteen semi-structured interviews were conducted with female board members. The resilience trajectories were analyzed considering three contexts: professional, organizational, and personal, in which sources of adversity and coping mechanisms were identified. Results: In the professional context, the low representation of women in leadership positions constituted one of the main sources of stress and adversity. In contrast, pursuing solid training in accounting proved to be a coping tool for serving on boards. In the organizational context, situations of harassment and gender bias appeared as sources of stress and adversity, whereas networking emerged as a coping mechanism for reaching leadership positions. Finally, in the personal context, self-imposed pressure to reconcile different roles was identified as an important source of stress and adversity, while family support and a challenge-oriented profile were the main coping factors. Contributions: The findings allow for a deeper understanding of the career paths of women accountants who reach the top of their executive careers, contributing to policies that promote gender equality.